Identification of Plant Soot as Novel Safe Feed Additive: Evaluation of 90-Day Oral Toxicity and Prenatal Developmental Toxicity in Rats - Pei, Xingyao; Xiao, Xilong; Liao, Jianling; Ke, Linfu; Li, Daowen; Tang, Shusheng (Frontiers in Veterinary Science, 2020)
Plant soot, as a novel feed additive, could not only improve digestive function but also adsorb mycotoxins and inhibit bacterial infections. The subchronic toxicity and prenatal developmental effects of plant soot were studied for the first time. Our results indicated that there was no subchronic toxicity in the range of 2,000–50,000 mg/kg plant soot added in the feed, and there was no significant difference in reproductive function, embryo development, and teratogenicity between the pregnant rats exposed to 312.5, 1,250, and 5,000 mg/kg plant soot and the control group. The maximum no-observed effect level (NOEL) of supplemental dosage in feed could be set to 50,000 mg/kg, and the maximum intragastric NOEL could be set to 5,000 mg/kg, which preliminarily provided guidance on daily additive amount or clinical protocols for plant soot, as well as promoting the development and application of this harmless antibiotic substitutes.